A quantitative model to predict blood use in adult orthotopic liver transplantation. Issue 3 (December 2015) - Liu, Chang; Vachharajani, Neeta; Song, Shuang; Cooke, Rhonda; Kangrga, Ivan; Chapman, William C.; Grossman, Brenda J.
Abstract: To identify preoperative predictors for the use of any blood component during and after orthotopic liver transplantation (OLT), we performed a retrospective analysis on 602 OLT patients who were randomly split into a training set (n = 482) and a validation set (n = 120). Hemoglobin and calculated MELD score were identified as independent predictors for blood use using bootstrap aggregation. A logistic regression model constructed using both variables showed comparable performance in the training and validation sets. Predictive scores can be obtained from a nomogram, and a score above −2.328 predicted transfusion of any blood component with a positive predictive value of 97% and 96% in the training and validation sets, respectively.